FRB Event Rate Predictions for the Ooty Wide Field Array - Bhattacharyya, S.; Bera, A.; Bharadwaj, S.; Bhat, Ramesh; Chengalur, J. (2017)
© 2017, Indian Academy of Sciences.We developed a generic formalism to estimate the event rate and the redshift distribution of Fast Radio Bursts (FRBs) in our previous publication (Bera et al. 2016), considering FRBs are of an extragalactic origin. In this paper, we present (a) the predicted pulse widths of FRBs by considering two different scattering models, (b) the minimum total energy required to detect events, (c) the redshift distribution and (d) the detection rates of FRBs for the Ooty Wide Field Array (OWFA). The energy spectrum of FRBs is modelled as a power law with an exponent -a and our analysis spans a range -3=a=5. We find that OWFA will be capable of detecting FRBs with a=0. The redshift distribution and the event rates of FRBs are estimated by assuming two different energy distribution functions; a Delta function and a Schechter luminosity function with an exponent -2=?=2. We consider an empirical scattering model based on pulsar observations (model I) as well as a theoretical model (model II) expected for the intergalactic medium. The redshift distributions peak at a particular redshift zp for a fixed value of a, which lie in the range 0.3=zp=1 for the scattering model I and remain flat and extend up to high redshifts (z?5) for the scattering model II.